To improve the ASTM standard of residual stress measurement using central hole drilling process by incorporating the effects of hole eccentricity - Khairul Azhari Sharifuddeen (2019)
Residual stress in materials may cause an engineer to make incorrect calculations and underestimate the integrity of a structure or model. There are many several ways of measuring residual stress. The most efficient and affordable method is the use of central hole drilling method. The method is semi destructive and can be implemented on a wide range of metals and situations. There are many factors contributing to the errors and measurement of the residual stress in Central Hole Drilling. There are also many procedures and method of calculation to achieve the residual stress results. The standard ASTM E837-13a regards a concentricity between the strain gauge rosette and the drilled hole, with a maximum allowable eccentricity of 0.004D of the diameter of the strain rosette. This value is exceptionally difficult to achieve when conducting experiments thus making the hole eccentricity one of the key cause of errors in the measurement. This report discusses the effects of hole eccentricity in the hole drilling method. A formulation is developed with MATLAB and Microsoft Excel to calculate the residual stress from a set of experimental strain data produced by the MTS 3000 RESTAN by SINT Technology. Four different method of calculation of the residual stresses will be compared. The formulation developed may possibly assist in future calculations of the residual stresses and further research of the Central hole drilling method.